ITC/EFPA Survey on test attitudes of psychologists - Evers, Arne (2011)
The manuscript on the attitude of psychologists with respect to tests in 17 European countries is accepted by all European Psychologists. The date of publication is unknown yet. After the original data gathering was closed, still two other European countries participated (Denmark and Hungary). The results of these 19 countries were presented in the symposium International Testing Practices (chaired by Jose Muniz). On initiative of the ITC the survey will be extended to countries all over the world.